A study on practices of mothers about scabies in children under five years of age - Lekha Aby, Aswathy (International Journal of Nursing Research, 2023)
Scabies remains a public health problem, especially in developing countries with a worldwide incidence of approximately 300 million cases each year. Prolonged skin-to-skin contact is necessary to allow the transmission of the causative mite. Aim: To assess the practices in relation to prevention and management of scabies among mothers of under five years of aged children, before and after planned teaching sprogramme To find the Significance of difference in pre and post-test overall practice score related to scabies. And to find out the association of post test practices in relation to prevention and management of scabies with selected demographic variable among mothers of under five children. Methods: A quasi experimental design were conducted for about 50 samples of mothers of children under five years of age by non probability convenient sampling technique, from paediatric medical ward of M G M Hospital, Kalamboli. M.G.M. Hospital. Data collection tool describes about the reported practices of mothers of under five children regarding the prevention and management of scabies. The reliability of the tool was established using test retest method and analyzed using Karl Pearson’s correlation coefficient formula. Results: During pre test in relation to prevention and management of scabies with regard to over all practices 48% of sample was in good category while 34% and 18% were in average and poor category which changed to 32% and 68% of very good and excellent category respectively during post test. A highly significant difference in the pre test and post test practices scores of the subjects in relation to prevention and management of scabies was found ‘P’ value is <0.0001. Hence the planned teaching is found to be effective in improving practices in relation to prevention and management of scabies among children under five.